2014
DOI: 10.5946/ce.2014.47.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Regimens for Gastrointestinal Endoscopy

Abstract: Sedation allows patients to tolerate unpleasant endoscopic procedures by relieving anxiety, discomfort, or pain. It also reduces a patient's risk of physical injury during endoscopic procedures, while providing the endoscopist with an adequate setting for a detailed examination. Sedation is therefore considered by many endoscopists to be an essential component of gastrointestinal endoscopy. Endoscopic sedation by nonanesthesiologists is a worldwide practice and has been proven effective and safe. Moderate seda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 25 publications
0
79
0
1
Order By: Relevance
“…[6] Although meperidine produces only mild hemodynamic depression, addition of meperidine to propofol may potentiate hypotension due to synergic action. [32] Previous studies have revealed that the use of larger initial bolus doses of propofol was associated with higher incidence of hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6] Although meperidine produces only mild hemodynamic depression, addition of meperidine to propofol may potentiate hypotension due to synergic action. [32] Previous studies have revealed that the use of larger initial bolus doses of propofol was associated with higher incidence of hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Although meperidine produces only mild hemodynamic depression, addition of meperidine to propofol may potentiate hypotension due to synergic action. [32] Previous studies have revealed that the use of larger initial bolus doses of propofol was associated with higher incidence of hypotension. [22][23][24][25][26][27][28][29][30] Hsieh et al [21] reported hypotension incidence as 23% for an initial bolus of 1 mg/kg propofol, which was then titrated in 10-20 mg increments plus 25 mg of meperidine (dose of propofol, 129.80±37.93 mg).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of effect for propofol is 0.5-1 minute, and the duration of effect is 4-8 minutes. 5 The pharmacokinetic parameters of propofol vary with patient factors such as weight, sex and age. The dose should be reduced in elderly patients.…”
Section: Pharmacology Of Propofolmentioning
confidence: 99%